Method of removal of colloid iron from groundwater of Western Siberia region by using of carbon dioxide; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Machekhina K. I. Ksenia Igorevna; Shiyan L. N. Lyudmila Nikolaevna; Tropina E. A. Elena Aleksandrovna; Voyno D. A. (2012, 2012)
Title screen